PROBLEMATIKA DALAM PELAKSANAAN PENANGGUHAN PENAHANAN ATAS PERMOHONAN KELUARGA TERSANGKA ATAU KUASA HUKUMNYA OLEH PENYIDIK POLRI - Ishadi P, M Deswan Nata (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT Implementation of Suspension Detention of suspects by investigators handled by Samarinda Police from year to year has decreased, it can be seen from that obtained from register Polda Balikpapan. This decline is due to the hard work of police officers in dealing with crime, so people are afraid of committing a crime or punishment errors. There are several reasons incurred in the letter of application for Suspension of Detention in order for the suspect to obtain Suspension of Detention, among others: The suspect will not run away and does not complicate the course of the examination; Collateral from the family, for the Suspension of Detention; The suspect will not cope with his actions again; The suspect has never been convicted; Still undergoing studies at educational institutions. Suspension of detention shall be the right of the suspect before his / her term of imprisonment, whereas the purpose of detention is to authorize the investigator and the public prosecutor and the judge to withhold against persons suspected or reasonably suspected of committing a crime. The purpose of detention is: To keep the fear of the suspect from giving birth; Keeping the suspect from harming or omitting evidence; Keep the suspect from repeating the crime again. In granting the request for suspension of detention, the investigator does not simply grant the request for suspension of detention, the investigator will see the case weight of the criminal offense committed by the suspect. Considerations of an investigator to accept or reject the request for suspension of detention include: Criminal acts committed by the suspect do not disturb the public: The suspect is still young, still in school or college. As for the suspension of detention may also occur if the suspect is enabled to: escape; where the suspect's residence is not fixed; if possible the suspect will remove evidence to obscure the inspection road either at the investigation level or at the other examination level; Not implementing the terms that have been agreed between the investigator and the suspect, such as reporting and so on. The obstacles faced by the investigator are as follows: The suspect ignores the provisions or conditions in the suspension of the holder; it is not clear the identity of the suspect and there is no guarantor for the suspect. Keywords: Suspension Hold Process.